Kegiatan peningkatan ekonomi melalui produksi olahan kakao dalam upaya pencegahan stunting - Setiawan, Noval Abdi; Hidayah, Taswin; Amelia, Rosa; Sejati, Hiro (JOURNAL of Public Health Concerns, 2025)
Background: Stunting remains a public health challenge in Indonesia, with a prevalence of 21.6% in 2022. Contributing factors include chronic malnutrition, recurrent infections, and low family purchasing power. In Ketapang Village, cocoa potential has not been optimally utilized, even though it could be developed into nutritious food with high economic value. Local cocoa processing is considered strategic for supporting Stunting prevention and improving community welfare. Purpose: Increase community income and prevent Stunting through entrepreneurship training, nutrition education, and diversification of processed cocoa products, such as Broka Brownies Cocoa, as a healthy food alternative based on local potential. Method: The 2025 KKL-PPM activity was conducted in Ketapang Village, Tanggamus, involving 25 housewives and village youth, supported by Posyandu (Integrated Service Post) cadres and village officials. Implementation methods included socialization of Stunting and balanced nutrition, training and practice in making Broka Brownies Cocoa using local ingredients, entrepreneurship mentoring (packaging, marketing, and small business management), and monitoring and evaluation of the activity's impact. The production process used simple tools and materials easily accessible to residents. Results: Community nutrition knowledge increased by approximately 30% and encouraged the production of Broka Brownies Cocoa by 25 participants with consistent quality. This innovative product was well-received by the community and provided added economic value, with a net profit margin of approximately 30% of production costs. The positive social impact was reflected in the formation of small business groups of housewives who independently continued production and marketing, demonstrating the potential for local empowerment based on functional foods. Conclusion: Nutrition literacy, cocoa processing skills, and the empowerment of community entrepreneurial potential through the Broka Brownies Cocoa innovation increased. This activity contributed to Stunting prevention, family economic empowerment, and the development of a competitive local culinary identity. Cross-sector collaboration and a local potential-based approach proved effective in creating sustainable solutions, with recommendations for further training, access to capital, and marketing networks to support business independence and village food security. Suggestion: The village government should support the formation of joint ventures and ongoing mentoring, and encourage the use of the product as a nutritious snack at integrated health posts (posyandu) and schools. Further research is needed to confirm the nutritional impact and sustainability of the program. Keywords: Community empowerment; Local potential; Nutrition; Socioeconomic; Stunting Pendahuluan: Stunting masih menjadi tantangan kesehatan masyarakat di Indonesia, dengan prevalensi 21.6% pada 2022. Faktor penyebabnya meliputi kekurangan gizi kronis, infeksi berulang, dan rendahnya daya beli keluarga. Di Desa Ketapang, potensi kakao belum dimanfaatkan optimal, padahal dapat dikembangkan menjadi pangan bergizi bernilai ekonomi tinggi. Pengolahan kakao lokal dinilai strategis untuk mendukung pencegahan stunting dan peningkatan kesejahteraan masyarakat. Tujuan: Meningkatkan pendapatan masyarakat dan mencegah stunting melalui pelatihan kewirausahaan, edukasi gizi, dan diversifikasi produk olahan kakao, seperti Broka Brownies Kakao, sebagai alternatif pangan sehat berbasis potensi lokal. Metode: Kegiatan KKL-PPM tahun 2025 dilaksanakan di Desa Ketapang, Tanggamus, dengan melibatkan 25 orang ibu rumah tangga dan pemuda desa, didukung oleh kader posyandu, dan perangkat desa. Metode pelaksanaan mencakup sosialisasi stunting dan gizi seimbang, pelatihan serta praktik pembuatan Broka Brownies Kakao berbahan lokal, pendampingan kewirausahaan (pengemasan, pemasaran, dan pengelolaan usaha kecil), serta monitoring dan evaluasi dampak kegiatan. Proses produksi menggunakan alat sederhana dan bahan yang mudah diakses warga. Hasil: Peningkatan pengetahuan gizi masyarakat sebesar ±30% dan mendorong produksi Broka Brownies Kakao oleh 25 peserta dengan kualitas seragam. Produk inovatif ini diterima baik oleh masyarakat dan memberikan nilai tambah ekonomi, dengan margin keuntungan bersih sekitar 30% dari biaya produksi. Dampak sosial positif tercermin dari terbentuknya kelompok usaha kecil ibu rumah tangga yang secara mandiri melanjutkan produksi dan pemasaran, menunjukkan potensi pemberdayaan lokal berbasis pangan fungsional. Simpulan: Terjadi peningkatan literasi gizi, keterampilan pengolahan kakao, dan pemberdayaan potensi kewirausahaan masyarakat melalui inovasi Broka Brownies Kakao. Kegiatan ini berkontribusi pada pencegahan stunting, penguatan ekonomi keluarga, dan pembentukan identitas kuliner lokal yang kompetitif. Kolaborasi lintas sektor serta pendekatan berbasis potensi lokal terbukti efektif menciptakan solusi berkelanjutan, dengan rekomendasi pelatihan lanjutan, akses permodalan, dan jejaring pemasaran untuk mendukung kemandirian usaha dan ketahanan pangan desa. Saran: Pemerintah desa perlu mendukung pembentukan usaha bersama dan pendampingan lanjutan, serta mendorong pemanfaatan produk sebagai camilan bergizi di posyandu dan sekolah. Penelitian lanjutan diperlukan untuk memastikan dampak gizi dan keberlanjutan program.